Modified lip repositioning: A surgical approach to treat the gummy smile - Aditya Gopinath Rao; Vijay Prasad Koganti; Ashok Kodangala Prabhakar; Sweta Soni (Wolters Kluwer Medknow Publications, 2015)
Gummy smile has been an esthetic concern for many patients. This clinical report describes a successful surgical coverage obtained by modified lip repositioning, thus surgically treating the gummy smile. The technique was performed to limit the retraction of elevator muscles (e.g., zygomaticus minor, orbicularis oris, leviator anguli oris and levator labi oris.) The technique is fulfilled by removing two strips of mucosa from maxillary buccal vestibule on both the sides leaving the frenum untouched and creating a partial thickness flap between mucogingival junction and upper lip musculature, and suturing the lip mucosa with mucogingival junction, resulting in a narrow vestibule and restricted muscle pull, thereby reducing gingival display. This technique is different from the conventional surgical lip repositioning as labial frenum is left untouched over here as it helps in maintain Litton the midline for lip repositioning and reduces the morbidity associated with it.